Mesoporous carbon structure impregnated with 2D engineered zirconium: A sustainable adsorbent for the removal of dyes from the aqueous solution. (15th July 2022) - Sonal, Sonalika; Acharya, Sourav; Mishra, Brijesh Kumar
Abstract: The key designing of new breeds of the adsorbents aimed to improve the physical, chemical and textural morphology along with surface functionalization, selectivity toward the contaminants, and regenerations efficiency. In this aspect, two adsorbents named wet oxidative and ultrasonicated zirconium impregnated composite, have been synthesized through two routes, i.e., wet oxidation and ultrasonication. In wet oxidation method, carbon-based materials are oxidized using an oxidant followed by impregnation, while in ultrasonication assisted route, the impregnation is carried out using acoustic phenomenon. The characterization study revealed that the wet oxidation process is more competent in impregnating zirconium and developing diverse porosity and functionalities. The maximum adsorption capacity of wet oxidative adsorbent was 812 mg/g for Reactive Blue 19 and 203.18 mg/g for Methylene Blue, that accentuated the efficiency of the adsorbent over raw activated carbon. The electrostatic interaction, hydrogen-bonding and ligand exchange phenomenon are the involved adsorption mechanism for dyes. The regeneration study finally asserts that the wet oxidative adsorbent shows an insignificant decrease in its capacity up to the 5 th -cycle (i.e., 87.67% removal at 5 th cycle) as compared to raw AC (46.71% removal at 5th cycle). Further, a continuous fixed-bed column study revealed a significant correlation between experimental breakthrough data and kinetic data. Thus, the developed adsorbent has a sedulous adsorption capacity to remove the most stubborn toxic dyes and can be used in industrial-scale applications. Graphical abstract: Image 1 Highlights: A highly efficient Zr-impregnated carbon-based adsorbent was synthesized through a facile route. Adsorbent endows highly competent textural and morphological features with oxidative functionalities. The adsorbent was imperatively creditable in anionic and cationic dyes adsorption through both batch and column studies. Different physicochemical interactions governed the adsorption mechanisms. The regeneration capacity up to the 5th cycle was impervious to its considerable decrease in adsorption capacity.